Digital Books Of Children's Literature As An Effort To Improve Literacy Of Reading In Elementary Schools - Khomsiyatun, Umi; Andayani; Suwandi, Sarwiji; Anindiarini, Atikah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The development of the times has brought children's literature to be introduced in the form of digital books. Digitizing children's literature is one of the efforts to increase the younger generation of a nation to be more literate. At the elementary education level. Digitizing children's literature books can be used in learning literary appreciation in grade 2 of elementary school. This study seeks to describe the relationship between digital books on children's literature as an effort to increase reading literacy in elementary schools. Based on this, this study used a descriptive qualitative method by collecting data through interviews and documentation. Analyzing this research through data reduction and data interpretation